Protective effects of moderate exercise with dietary vitamin C and E on blood antioxidative defense mechanism in rats with streptozotocin-induced diabetes - Naziroglu, M; Butterworth, PJ (Human Kinetics Publ Inc, 2005)
Daily moderate exercise and supplementation of vitamins C and E (VCE) can be beneficial in diabetes by ameliorating the effects of free radical production. The present study sought to analyze the effect of moderate exercise accompanying VCE supplementation on lipid peroxidation (LP) and antioxidative systems in the blood of streptozotocin-induced diabetic rats. Forty female Wistar rats were randomly divided 4 groups. The 1st and 2nd groups served as the control and diabetic groups, respectively. The 3rd group was the diabetic-exercise group. The 4th group, also diabetic-exercise rats, received VCE-supplemented feed. Animals in the exercised groups were moderately exercised on a treadmill 5 days a week for 3 weeks. Diabetes was induced on Day 0 of the exercise. Plasma and red blood cell (RBC) samples were taken from all animals on Day 20. Glutathione peroxidase, catalase, and reduced glutathione levels in plasma and RBCs, and vitamins A, E, and beta-carotene in plasma were lower in diabetic rats than in control animals, whereas there was a significant increase in platelet counts in both plasma and RBC LP levels. The decreased antioxidant enzymes and vitamins, and the increased LP levels and WBC counts, did improve through exercise only, although their levels were mostly increased by exercise + VCE supplementation. There were no significant changes in the hemoglobin and hematocrit values in the 4 groups. In conclusion, these data demonstrate an increase in LP in the blood of diabetic animals whereas there was a decrease in the antioxidant vitamins and enzymes. However, dietary VCE with moderate exercise may strengthen the antioxidant defense system by decreasing reactive oxygen species.
Keywords: hyperglycemia; glutathione peroxidase; oxidative stress; hematological values